Long-Term Function of Genetically Modified Porcine Neonatal Islet Xenografts in Baboons. (July 2018) - Hawthorne, Wayne; Burns, Heather; Chew, Yi Vee; Salvaris, Evelyn; Ayoubi, Ali; Hawkes, Joanne; Brady, Jamie; Barlow, Helen; Yi, Shounan; Hu, Min; Lew, Andrew; O'Connell, Philip; et al.
Abstract : Introduction: In xenotransplantation the stringent pig-to-baboon islet xenograft preclinical model is a difficult one with the maximum period of normoglycemia reported to only 1 day. Previously we have shown that neonatal islet cell clusters (NICC) from GTKO/CD55-CD59-HT pigs prevent both hyper acute rejection (HAR) and the instant blood mediated inflammatory response (IBMIR) in immunosuppressed baboons. However, the maturation and function of the NICC were not examined in detail in the initial study, because (i) the recipients were not diabetic, and (ii) the standard clinical-based immunosuppression used was insufficient to prevent biopsy-proven rejection within 1 month. In the current study, therefore, we used streptozotocin-induced diabetic recipients and changed to a costimulation blockade-based immunosuppressive regimen. Aims: To achieve long-term normoglycemia in diabetic baboons transplanted with neonatal pig islets, and to investigate the effect of ceasing immunosuppression. Materials and Methods: Five diabetic baboons received intraportal infusion of NICC (10, 000-50, 000 IEQ/kg) from 1-5 day old GTKO/CD55-CD59-HT piglets. From day -3 recipients were treated with anti-CD2 induction and subsequently maintenance with oral tacrolimus, anti-CD154 and belatacept, which were progressively ceased. Graft survival and function was followed by daily blood sugar levels (BSL), IVGTT, OGTT and immunohistochemical analysis of liver biopsies taken at various time points over the study period. Results and Discussion: None of the baboons exhibited signs of thrombosis associated with IBMIR, with no change to platelet counts, vWF, fibrinogen or D-dimer levels from baseline. Recipients developed normal fasting BSL and had normal IVGTT and OGTT, with porcine insulin and C-peptide secreted in response to glucose bolus stimulus. All animals have become normoglycaemic off all exogenous insulin. Liver biopsies revealed strong positive staining for insulin, glucagon and somatostatin in xenografts. One recipient receiving 50, 000 IEQ/kg was insulin-independent for >7 months, including 7 weeks after the last drug (belatacept) was ceased. A second recipient receiving 10, 000 IEQ/kg took longer to achieve insulin independence, but remained insulin independent >18 months, including 6-months off all immunosuppression. The fourth and fifth animals are being followed out past 6-months and 2-months post transplant. Conclusion: We have confirmed that GTKO/CD55-CD59-HT neonatal islets are protected from IBMIR in the baboon model. More importantly, we have demonstrated for the first time long-term survival and function of porcine islets in baboons. The costimulation blockade-based immunosuppression permitted maturation of the islets such that the dose required to achieve normoglycemia (10, 000 IEQ/kg) was lower than that reported in any NHP model. Remarkably, this recipient remained normoglycemic for 6 months after immunosuppression was ceased. Bristol-Myers Squibb Company for donation of Belatacept, . Keith Reimann at NIH Nonhuman Primate Reagent Resource for supply of Anti CD154 antibody.